2015
DOI: 10.1080/21513732.2014.998284
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vegetation response to grazing management in arid rangelands of southern Tunisia

Abstract: Livestock grazing influences arid rangelands greatly with important effects on vegetation dynamics. Two areas traditionally grazed by sheep and goats in southern Tunisia were sampled to evaluate the vegetation response to grazing management. A continuous grazing (CG) area was sampled in March 2007. A 2000 ha exclosure that had been rested for 3 years (2004-2007), grazed for 2 months (July and August 2007), and then rested for 7 months (September 2007 to February 2008) was sampled before and after grazing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Le Houérou () suggested that the RUE was below 1 kg DM ha −1 mm −1 in degraded rangelands. This finding has been recently reviewed by many studies showing that protection and moderate grazing may increase rangeland productivity (Gamoun et al, ; Gamoun, , ; Gamoun et al, ). While under average rainfall condition, defoliation increased RUE in long‐term lightly, but not heavily, grazed treatment (Varnamkhasti et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Le Houérou () suggested that the RUE was below 1 kg DM ha −1 mm −1 in degraded rangelands. This finding has been recently reviewed by many studies showing that protection and moderate grazing may increase rangeland productivity (Gamoun et al, ; Gamoun, , ; Gamoun et al, ). While under average rainfall condition, defoliation increased RUE in long‐term lightly, but not heavily, grazed treatment (Varnamkhasti et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous species of ephemeral and annual appear after rains, complete their life cycle in a short duration and vanish. These species, as well important in nutritional contribution also decrease grazing pressure on palatable perennial browse species (Gamoun et al, 2015).…”
Section: Palatability Classification Of Browsesmentioning
confidence: 99%
“…In fact, most rangeland improvement projects in southern Tunisia are using the resting technique (locally known as Gdel or Hima) to restore degraded arid rangelands [14]. This technique is considered by many authors among the most cost-effective restoration practices [7,14,15]. Under the Hima system, the grazing land is protected by the local pastoral communities from livestock grazing and wood harvesting for a certain period of time.…”
Section: Introductionmentioning
confidence: 99%